When the Flag Fails: Reassessing Flag State Responsibility for Marine Pollution by the Shadow Fleet - Fitriani, Nazwa; Danial, Danial; Vitrana, Mokhamad Gisa; Hambali, Hambali (Faculty of Law, Universitas Jambi, 2026)
Background: Shadow fleet threatens Indonesia’s maritime sovereignty, particularly in cases of marine pollution caused by vessel activities. Incidents involving MT Arman 114 and MT Freya reveal gaps in flag state responsibility that infringes upon Indonesian waters. In this context, tensions emerge between coastal State stability and flag State obligations, exacerbated by the evasive and regulatory-avoidant characteristics of shadow fleet operations. Methodology: This study employs a normative legal methodology using both a statutory and a conceptual approach. The secondary data are derived from instruments such as the 1982 UNCLOS, MARPOL 73/78, the 2001 ILC Draft, the 1974 SOLAS, as well as Indonesian regulations, namely Law No. 17 of 2008 and Law No. 32 of 2009, and relevant legal principles. The data are analyzed qualitatively to assess the conformity between das sollen and das sein. Objectives: This research discusses the legal implications of the shadow fleet regarding Indonesia’s maritime sovereignty. It principally examines how effectively the UNCLOS framework governs flag State responsibility for shadow fleet concerning the risk of marine pollution ion coastal State waters. Findings: UNCLOS establishes the flag state’s responsibility for marine pollution resulting from shadow fleet practices through the genuine link principle. In practice, however, remediation burdens frequently shift to coastal States and private actorsm as flag States often fail to discharge their obligations. Novelty: This research provides a distinct scholarly contribution by examining the foundational dimension of the implications of environmentally harmful shadow fleet practices, specifically the responsibility of the flag State.